Return on equity determinants and Covid-19 pandemic impacts on Latin America companies: A panel data study - Lebre-Rodrigues, Claudia; Nakamura, Wilson Toshiro; Mendes, Johnny Silva (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This research investigates the determinants of ROE and the impact caused by the Covid-19 pandemic on public companies in Latin America. The fixed effects regression model with panel data is used to identify that factors related to sales policies and cost controls are the ones that contribute the most to ROE performance, regardless of the period. On the other hand, the level of indebtedness and macroeconomic indicators are not significant, strengthening the finding that the operational and internal decisions of the company contribute more strongly to maximizing shareholder returns. This verification helps financial managers in directing decisions and expands academic knowledge on this topic.